The feasibility of using smartphone apps to manage self-harm and suicidal acts in adolescents admitted to an inpatient mental health ward. (November 2020) - Muscara, Frank; Ng, Olivia; Crossley, Louise; Lu, Sinh; Kalisch, Lauren; Melvin, Glenn; Gronow, Sam; Prakash, Chidambaram; Anderson, Vicki
Objective: The aim of this study is to assess the feasibility (uptake, retention and adherence) and acceptability of a combination of smartphone apps to deliver a digitized safety plan, BeyondNow, and personalized management strategies, BlueIce, with adolescents discharged from a mental health inpatient ward following self-harm, suicidal ideation and/or behavior. Methods: Participants in this pre-post pilot study included 20 adolescents between 13–18 years, presenting with self-harming or suicidal behaviors in an inpatient psychiatric ward at a tertiary pediatric hospital. Participants were familiarized with the apps and completed baseline measures prior to discharge. They used the apps for six weeks before completing the follow-up survey, which measured feasibility and acceptability of the apps, as well as suicide resilience. Results: Seventeen participants completed the pilot. Most of the sample accessed both apps at least once, three accessed the BeyondNow safety plan five times or more, and six used the BlueIce toolbox five times or more. A total of 73.5% of the sample that experienced a crisis used at least one of the apps at least once. Forty seven percent felt that the apps would not keep them safe when in crisis, although almost all of the sample rated both apps as easy to use (94% for BeyondNow, and 82% for BlueIce). Medium to large effect sizes were also found with regard to improvements in suicide resilience. Conclusion: Both apps were found to be feasible and acceptable in this population, and easy to use, although no conclusions can be drawn regarding the clinical efficacy of the apps.